1973
DOI: 10.1177/030098587301000208
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Calf Diarrhea. Electron Microscopy of Intestines Infected with a Reovirus-Like Agent

Abstract: Abstract. Neonatal calf diarrhea induced by a reovirus-like agent was studied by electron microscopy. Gnotobiotic calves were inoculated with virulent and cell-cultureadapted isolates of viruses, and similar results were obtained with both isolates. The virus infected mature villous epithelial cells of the small intestine and replicated predominantly within cisternae of the endoplasmic reticulum. Macrophages within small intestinal villi also contained viral particles. Shedding of virus into the feces apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
1
1

Year Published

1976
1976
2001
2001

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 5 publications
(7 reference statements)
6
52
1
1
Order By: Relevance
“…The demonstration of rotavirus replication in phagocytic cells agrees with reports by different investigators who described the presence of rotavirus particles in subepithelial phagocytic cells, suggesting that this may be a mechanism of virus interaction with the immune system (5)(6)(7)13,14). The observation of rotavirus replication in phagocytic cells but the absence of viral replication in MA-104 cells inoculated with the lysate of these phagocytic cells suggests the production of defective viral particles.…”
supporting
confidence: 90%
“…The demonstration of rotavirus replication in phagocytic cells agrees with reports by different investigators who described the presence of rotavirus particles in subepithelial phagocytic cells, suggesting that this may be a mechanism of virus interaction with the immune system (5)(6)(7)13,14). The observation of rotavirus replication in phagocytic cells but the absence of viral replication in MA-104 cells inoculated with the lysate of these phagocytic cells suggests the production of defective viral particles.…”
supporting
confidence: 90%
“…Bovine coronavirus (BCV) is an enteric virus which multiplies in the differentiated enterocytes of the small intestine and colon, causing acute enteritis in newborn calves (Stair et aL, 1972;Babiuk et al, 1985) and chronic shedding (Crouch et al, 1985) or diarrhoea (Takahashi et aL, 1980) in adult cows. BCV particles consist of large single-stranded positive RNA (30 kb) associated with a basic phosphonucleoprotein (N, Mr 52K) forming a helical ribonucleoprotein protected by a viral envelope containing three glycoproteins, M, S and HE (Laporte & Bobulesco, 1981;King & Brian, 1982;.…”
Section: Introductionmentioning
confidence: 99%
“…Coronaviruses have been implicated in the aetiology of human gastroenteritis (Caul & Clarke, 1975;Caul et al, 1975;Caul & Egglestone, 1977;Lennartz et al, 1978). Neonatal calf diarrhoea coronavirus (NCDCV) is an important cause of diarrhoea in newborn calves (Stair et al, 1972;Mebus et al, 1973), but antiviral activity to NCDCV has been found in human sera, suggesting a possible role of a related coronavirus in gastroenteritis of humans (Sharpee & Mebus, 1975;Kaye et al, 1975). In addition, a close antigenic relationship between OC43 and NCDCV (both adapted to growth in suckling mouse brain) has been detected using complement-fixation, haemagglutination-inhibition (HI) and neutralization tests (Kaye et al, 1975).…”
Section: Introductionmentioning
confidence: 99%